Enhancing The Character of Students Through The Implementation of 2013 Curriculum at SMK Negeri 1 Siatas Barita - Andrianus Nababan (Universitas Kristen Satya Wacana, 2020)
The research is aimed to investigate the extent of the Implementation of 2013 Curriculum in improving students’ character at the State Vocational School in Siatas Barita District, North Tapanuli Regency. The number of participants who involved in this study was 209 students. Data was collected by questionare and analyzed with using desricptive analysis. The result of study revealed that there is the improvement of students’ character after implementing the 2013 curriculum. More particularly, the improvement of students’ character is accord with the Pancasila and religious values. In term of the religious values, Christian education which was taught by the Christian education teachers throught implementing the 2013 curriculum significantly influence to students’ character. Based on the result of this study, Christian religious education teachers should involve more students in learning process so that students can understand how to have a good character. Recommendations for the further study and practice were discussed.